El desarrollo de la efectividad comunicativa escrita en ELE: las arabófonas a examen - Boillos Pereira, Mari Mar (Logos (La Serena, Chile), 2020)
Communicative effectiveness in foreign language writing refers to the ability to dominate a multidimensional system that includes linguistic, sociolinguistic, and pragmatic knowledge. This work focuses on measuring the efficacy in Lebanese Spanish students’ writing throughout different stages. All students’ mother tongue is Arabic. For this purpose, a scale of measurement of communicative effectiveness has been applied in the texts written by 57 university students. The results attest an incidence of the level in the grammar domain, whereas this one does not seem to have an impact on the structure of the text, the recognition of the rhetorical situation or the selection of the ideas.